Ab initio simulations of the structure of thin water layers on defective anatase TiO2(101) surfaces. Issue 18 (20th April 2015) - Aschauer, Ulrich Johannes; Tilocca, Antonio; Selloni, Annabella; Eisenstein, Odile; Fliegl, Heike; Hopmann, Kathrin H.; Mennucci, Benedetta
<x xml:space="preserve">Abstract</x> Titania–water interfaces are important in various fields of science, from geophysics to photocatalysis and biochemistry. Here, we use ab initio molecular dynamics simulations to investigate the structure of thin water overlayers on the (101) surface of TiO2 anatase in the presence of oxidizing defects. For comparison, results of our previous studies of water layers on defect‐free and reduced anatase (101) are also reviewed. On the stoichiometric defect‐free surface‐ordered structures are formed at one and two monolayer coverage, and the order in the first bilayer is largely maintained when a third water layer is adsorbed. By contrast, the vertical and in‐plane ordering of the water layers is strongly perturbed in the presence of both oxidizing and reducing defects. As a result, the structure of the water layer is much more diffuse under these conditions, and frequent exchanges of water molecules between different layers are observed. © 2015 Wiley Periodicals, Inc.